Komunikatory internetowe w zastosowaniach biznesowych - Watras, Grażyna (Internet communicators in business applications, 2005)
This paper presents universal and specialized communicators which are used by polish companies. They may function as an ASP at Small and Medium Enterprises (SME) and a corporate at large companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 270-276